Pengaruh Karakteristik Perusahaan Terhadap Tingkat Pengungkapan Aset Biologis Berdasarkan PSAK 69 - Setiyawan, Adi; Maslichah, Maslichah; Hidayati, Irma (Universitas Islam Malang, 2024)
This study aims to analyze the influence of company characteristics, consisting of biological asset intensity, firm size, and type of public accounting firm, on the level of biological asset disclosure in agricultural sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2022 period. The purposive sampling technique was used in this study. This study uses secondary data obtained through documentation techniques, namely by collecting information from company financial statements during the specified period. This study uses a quantitative method with multiple linear regression analysis processed using SPSS version 25. The results show that simultaneously, biological asset intensity, firm size, and type of public accounting firm have an influence on the level of biological asset disclosure. Partially, biological asset intensity does not affect the level of biological asset disclosure, while firm size and type of public accounting firm do affect the level of biological asset disclosure in agricultural companies listed on the IDX during the period studied.Keywords: Biological asset intensity, firm size, type of public accounting firm, biological asset disclosure, agricultural sector companies.